Methylisoindigo and Its Bromo-Derivatives Are Selective Tyrosine Kinase Inhibitors, Repressing Cellular Stat3 Activity, and Target CD133+ Cancer Stem Cells in PDAC - Tegethoff, Jana (Molecules, 2017)
Indirubin is an active component of the herbal ingredient ‘Danggui Longhui wan’, which was used for the treatment of inflammation and chronic myeloid leukemia in China. The recent study showed its derivative methylisoindigo (also known as meisoindigo) preferentially targeting cancer stem cells (CSCs) in interference with AMPK and LKB1, the cellular metabolic sensors. In this study, we screened the effect of meisoindigo on a panel of 300 protein kinases and found that it selectively inhibited Stat3-associated tyrosine kinases and further confirmed its activity in cell based assays. To gain a deeper insight into the structure–activity relationship we produced 7 bromo-derivatives exhausting the accessible positions on the bisindole backbone except for in the 4-position due to the space limitation. We compared their anti-proliferative effects on tumor cells. We found that 6-bromomeisoindigo showed improved toxicity in company with increased Stat3 inhibition. Moreover, we detected that 6-bromomeisoindigo induced apoptosis of 95% of CD133+ pancreatic cancer cells. Considering that CD133 is a common marker highly expressed in a range of CSCs, our results imply the potential application of 6-bromomeisoindigo for the treatment of CSCs in different types of cancers.